(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
This paper presents an experimental investigation on the structural behavior of continuous steel-reactive powder concrete composite member under repeated loads. Composite-beam, including one steel I-beam and concrete slab, which are jointed together by shear connector. The study was conducted in experimental and theoretical parts. The concrete deck slab was connected to steel I-beams by headed steel studs welded to the top flanges of the steel I-beams. The dimensions of the deck slab are (2200×250×80mm: length×width×thickness), while the type of I-beam is (IPE 140) with length of (2200mm). To study the continuous steel-reactive powder concrete composite member such as the ultimate load carrying capacity, deflection and crack pattern at the ultimate load, six different types of beams were tested. The parameters of the study were type of concrete (RPC and Normal Concrete (NC)), type of loading, type of boundary condition and different number of shear connector. In the theoretical part, the tested beams were numerically modeled then analyzed using the finite element method. The numerical models were carried out in three dimensions of the software package (ANSYS 16.1). The results of the study indicate that the general trend in ultimate load is to decrease with (use normal concrete, test under repeated load, use simply supports and reduce the number of shear connectors), by (23.4, 9.2, 42.4, 18.7 and 23.15) % respectively.